Strengthening outcome-based education: Capability approach perspective - Dano, Givheart (Papanda Publisher, 2024)
This paper explores the integration of the Capability Approach into Outcome-Based Education (OBE) to enhance the quality and inclusivity of educational practices. While OBE has gained acceptance for its structured approach, critics raise concerns about its potential limitations in fostering holistic development. The Capability Approach, rooted in the work of Amartya Sen and Martha Nussbaum, offers an alternative perspective, emphasizing human capabilities and freedoms. The paper advocates for a broader view of education, asserting that it should empower learners with skills beyond predefined outcomes. It discusses the theoretical foundations of both approaches, their key principles, and the potential synergies between them. The study employs a comprehensive qualitative methodology, analyzing various sources to enrich the understanding of the research topic. Criticisms of OBE include a perceived narrowing of the curriculum and concerns about its impact on individual excellence. Case studies from different countries highlight challenges and varying outcomes in OBE implementation. The integration of the Capability Approach into OBE is proposed as a transformative avenue, emphasizing the cultivation of capabilities alongside traditional knowledge. Practical implications are outlined, including designing comprehensive learning outcomes, adapting curriculum and pedagogy, and employing diverse assessment methods. The integrated approach is seen as a means to empower learners for personal and societal flourishing, fostering inclusivity and equity in education. The paper concludes that this integration signifies a paradigm shift, redefining education as a transformative force for individual and societal progress.